Early Enhancement of Neuroplasticity Index, the Ratio of Serum Brain-Derived Neurotrophic Factor Level to HAMD-24 Score, in Predicting the Long-Term Antidepressant Efficacy - Zhang, Yuxuan; Cui, Bo; Wang, Tianyu; Lu, Yan; Chen, Zhenlin; Zou, Zhilu; Miao, Jinlin; Zhao, Xiuli; Yuan, Yonggui; Wang, Haosen; Chen, Gang (Frontiers in Behavioral Neuroscience, 2021)
Background: Current mainstream treatment of major depressive disorder (MDD) has a disadvantage in delayed onset of efficacy, making detection of early signatures predicative of the long-term treatment efficacy urgent. Methods: MDD patients were scored with HAMD-24 and serum brain-derived neurotrophic factor (BDNF) levels were measured at different times in two independent trials: a single-arm observation of Yueju pill, a clinically approved traditional multiherbal medicine, and a two-arm random placebo-controlled trial for Yueju vs escitalopram. The ratio of the BDNF level to HAMD-24 score, or neuroplasticity index (NI), and its derived parameters were used for correlation analysis and receiver operating characteristic (ROC) analysis. Results: On both the early (4th) and final (28th) days, Yueju and escitalopram significantly reduced HAMD-24 scores, compared to baselines, but only Yueju increased BDNF at both times. For either Yueju or escitalopram treatment, NI, but not BDNF, at baseline was correlated to NIs at the early or final treatment day. NI at early time was significantly correlated to early NI enhancement from the baseline for both Yueju and escitalopram, and to final NI enhancement from the baseline for Yueju in both trials. ROC analysis supported the predictability of Yueju’s final treatment efficacy from early NI enhancement. Limitations: The small sample size and 28 days of treatment time may lead to the impossibility of ROC analysis of escitalopram. Conclusion: Early NI enhancement is useful for prediction of long-term efficacy of Yueju and presumably some other antidepressants. Clinical Trial Registration: [www.ClinicalTrials.gov], identifier [ChiCTR1900021114].